Enabling mass surveillance: data aggregation in the age of big data and the Internet of Things. Issue 2 (4th May 2019) - Maras, Marie-Helen; Wandt, Adam Scott
ABSTRACT: The Internet of Things as envisioned – that is, an interconnected, interdependent and interoperable networked world – creates inherent dangers. Among these dangers, is the fact that it facilitates perpetual surveillance of populations. This form of surveillance is made possible because IoT devices record and transmit a massive amount of data that is being shared and analysed in new and unique ways to enable the ubiquitous monitoring of individuals. Ultimately, the data collected by the Internet of Things enables a level of surveillance previously only written about in science fiction novels. This article examines the privacy implications of this 'new norm' of perpetual surveillance, the private sector's primary role in enabling, and engaging in, this surveillance, and what, if anything, can be done about this surveillance.